2021
DOI: 10.1007/s00432-021-03846-6
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy following combined induction chemotherapy and concurrent chemoradiotherapy improves survival in N2–3-positive nasopharyngeal carcinoma patients

Abstract: Objective: This study aimed to explore the clinical value of adjuvant chemotherapy (ACT) in locoregionally advanced nasopharyngeal carcinoma (LANC) following concurrent chemoradiotherapy (CCRT) and induction chemotherapy (ICT).Methods: We included 839 newly diagnosed LANC patients in the study. ICT plus CCRT (ICT+CCRT group) was administered to 443 patients and 396 patients who received ACT after receiving ICT plus CCRT (ICT+CCRT+ACT group). Univariate and multivariate Cox regression analyses were carried out … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…However, we used PSM to balance the two cohorts of patients who underwent the IC+CCRT or IC+CCRT+AC/MC therapeutic protocol, and the results showed that two cohorts have similar survival outcomes. This result is consistent with Zou et al's and Tao et al's study 10,38 . Chen et al performed a study to explore the correlation between postradiotherapy (RT) EB‐DNA levels and AC with cisplatin plus gemcitabine, and they found that AC did not benefit patients who had high levels of EB‐DNA after RT 39 .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…However, we used PSM to balance the two cohorts of patients who underwent the IC+CCRT or IC+CCRT+AC/MC therapeutic protocol, and the results showed that two cohorts have similar survival outcomes. This result is consistent with Zou et al's and Tao et al's study 10,38 . Chen et al performed a study to explore the correlation between postradiotherapy (RT) EB‐DNA levels and AC with cisplatin plus gemcitabine, and they found that AC did not benefit patients who had high levels of EB‐DNA after RT 39 .…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, Zhang et al and Tao et al showed that AC using TP was an effective treatment option for LA‐NPC patients, and most patients tolerated it. 10 , 35 Cisplatin plus 5‐fluorouracil (PF) is the only AC treatment option recommended by the NCCN guidelines to date. 4 5‐Fluorouracil can effectively damage tumor cells since it can inhibit thymidine synthase and affect DNA synthesis and is widely used in a variety of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations